2021
DOI: 10.1371/journal.pone.0247824
|View full text |Cite
|
Sign up to set email alerts
|

A classic approach for determining genomic prediction accuracy under terminal drought stress and well-watered conditions in wheat landraces and cultivars

Abstract: The present study aimed to improve the accuracy of genomic prediction of 16 agronomic traits in a diverse bread wheat (Triticum aestivum L.) germplasm under terminal drought stress and well-watered conditions in semi-arid environments. An association panel including 87 bread wheat cultivars and 199 landraces from Iran bread wheat germplasm was planted under two irrigation systems in semi-arid climate zones. The whole association panel was genotyped with 9047 single nucleotide polymorphism markers using the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Generally speaking, the GP accuracy depends on several factors, including the LD levels, genetic diversity in populations, genomic selection methodology, and the genetic architecture of the trait [ 42 ]. In the recent study, we found that GBLUP appeared as better than RR-BLUP and BRR, reflecting that GBLUP is a potent model for implementing genomic selection in wheat accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the GP accuracy depends on several factors, including the LD levels, genetic diversity in populations, genomic selection methodology, and the genetic architecture of the trait [ 42 ]. In the recent study, we found that GBLUP appeared as better than RR-BLUP and BRR, reflecting that GBLUP is a potent model for implementing genomic selection in wheat accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, obtaining the best outcomes from the breeding value-based methods depend on the genetic architecture of trait, genetic variation, etc. [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that gBLUP and rrBLUP are similar models. One of the advantages of gBLUP over rrBLUP is the reduction of the dimensions of the mixed equations to the number of people in the reference population, the calculation of accuracy and error predicting corrective values ​​as commonly used in pedigree methods and combining The information of genotyped and non-genotyped individuals was mentioned simultaneously in the mixed equations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations